Building Trust in Media Coverage of Security Issues in Nigeria - Olulesi, Abimbola (Budapest International Research and Critics University, 2025)
The media in a democratic setting exists to inform, educate and entertain the general public. The media are referred to as the Fourth Estate of the nation with oversight functions on the activities of the Executive, Legislature and Judiciary. Despite the return to democratic governance in 1999, Nigeria has witnessed an increase in security challenges, from the Sharia based riots in 1999, Sagamu riots in 2000, the Jos riots in 2008, through the Chibok girls abduction by Boko Haram insurgents in 2014 to the Kaduna Shite clashes with the Army in 2015. Till date, majority of the over 200 secondary school girls abducted at Chibok still remain in captivity. The objective of this study is to examine to what extent the Nigerian media has played the role of agenda setting through media reports that adhere to objectivity, truth and balance. This study adopted the content analysis method of media reports on security challenges and discovered that, such issues as media ownership, poor remuneration of media practitioners, corruption, religion and ethnicity tend to colour media reports which negatively impacts on the quality of and adherence to ethics of media coverage. This results in the discerning public treating such reports with little or no trust. This report recommends the improvement in the remuneration of media practitioners, effective implementation of freedom of information act, regular media summits on coverage of conflicts, co-operation of the security agencies with the media and a strict adherence to ethics of media as definitive steps that need to be urgently implemented in restoring the lost trust in media coverage of conflicts in Nigeria. In addition, media bodies such as the Nigerian Broadcasting Corporation (NBC) and the Nigeria Union of Journalists (NUJ) must lead the fight in ensuring ethical journalism thrives and ownership does not become an albatross to the industry.